Response of Food Barley (Hordeum vulgare L) to NPS and Nitrogen (N) under limed conditions of acid soils at highland of Guji, Southern Ethiopia - Seyoum Alemu; Yared Tesfaye; Aliyi Kedir (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Barley is one of the major crops produced in Ethiopia in general and in specific in the study area. Even though it is such an important and major crop in the study area, its yield is very low due to many production constraints which include a lack of improved varieties, poor agronomic practice, Soil acidity problems, diseases, weeds, and low soil fertility in many parts of Ethiopia including Guji zone. The activity was conducted during the 2019-2021 main cropping season at Bore with the objective of determining the effect of NPS and N fertilizer rates on yield components and yield of Food Barley under limed conditions of acidic soil for highlands. The experiment was laid out in a split-plot design with three replications using the HB1307 Food Barley variety as a test crop. Four levels of NPS (0, 50, 100, and 150 kg ha-1) and four levels of N (0, 23, 46, and 69 kg ha-1) was used for these treatments which make a total of 16 treatment under limed and unlimed conditions. Analysis of the results revealed that all parameters were significantly (p < 0.05) affected by the interaction of the factors (NPS, N, and liming) as well as the main effects except date to 50% heading and days to maturity which did not significantly (p < 0.05) affected. The highest grain yield (3862 kg/ha) was obtained from the combination of 100 kg/ha NPS and 23 kg/ha. Therefore, the use of 100 kg ha-1 NPS and 23 kg ha-1 N is recommended for food barley production in the study area and other areas with similar agroecologies.